Perception, conceptual knowledge and competency level of integrated science process skill towards planning a professional enhancement programme - Edy Hafizan; Lilia Halim; Subahan Meerah, T (Universiti Kebangsaan Malaysia, 2012)
Science curriculum that emphasizes science process skills (SPS) will be able to help students acquire and understand information, as well as improve skills in critical thinking and decision making. Consequently, the SPS should be systematically taught to the students from as early as at primary school. To produce students who acquire the science process skills, the teacher should be competent in SPS; theoretically and practically. Thus, the aim of this study was to identify the teachers’ perception on their understanding of integrated SPS, conceptual knowledge and the competence level of integrated SPS of primary school teachers in Kuala Lumpur. A questionnaire was administered to 329 science teachers from 52 primary schools that have been selected randomly. The reliability of the instrument is 0.80. The data were analyzed using descriptive and inferential analysis (t-test and ANOVA). The findings showed that majority of teachers (74.1% to 83.6%) perceived that they have a high level of understanding on each of the sub-component of an integrated SPS. However teachers’ perception on their level of understanding of the integrated SPS was found to be inconsistent with the actual level of understanding (conceptual knowledge). Teachers had a low level of conceptual understanding of the integrated SPS. The findings also revealed that science teachers did not have sufficient conceptual knowledge of integrated SPS to teach their students to understand it in a meaningful way. However, the competency level of the integrated SPS among teachers is high with a mean of 20.86. As a conclusion, the study showed that teachers competency in the integrated SPS is good at the practical stage but not theoretically. Therefore, emphasis should be given to integrated SPS both conceptual and operational knowledge in pre and in-service training to ensure that the teachers understand, acquire and are able to implement the skills meaningfully.